ANALISIS PENGGUNAAN AIR BERSIH, MENCUCI TANGAN, MEMBUANG TINJA DENGAN KEJADIAN DIARE PADA BALITA - Fatmawati, Tina Yuli; Indrawati, Iin Indrawati; Ariyanto, Ariyanto Ariyanto (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2017)
Diarrhea is a major cause of morbidity and mortality in children in developing countries, with an estimated 1.3 billion episodes and 3.2 million deaths annually in infants. One effort to prevent the case of diarrhea is to behave Clean and Healthy Life (PHBS). The purpose of this study to determine the relationship of cleaning water use, washing hands and dispose of the correct stool with the incidence of diarrhea in infants. The method of this research is quantitative analytic with cross sectional design, the number of samples of mothers who have children 1-5 years old in RT 01 and 39 Subdistrict Kenali Asam Bawah total 56, sampling using total sampling. Data collection techniques using questionnaires, technique of data analysis using univariate and bivariate. The result of this research showed that the respondents had PHBS based on good water usage of 47 people (83.9%). Respondents had PHBS based on hand washing with 32 persons (57.1%). Respondents had PHBS based on Disposing of feces well 17 people (30.4% ). There was no correlation between clean water use and diarrhea occurrence with p-valueÂ = 0,907, hand washing relationship with diarrhea occurrence at under five years with p-value = 0,006, there was correlation of feces disposal correctly with diarrhea incidence in under fives with p- Value = 0,000.